1998
DOI: 10.1093/oxfordjournals.jbchem.a022107
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of Human Tissue Plasminogen Activator (t-PA) with Pregnancy Zone Protein: A Comparative Study with t-PA-  2 -Macroglobulin Interaction

Abstract: Human pregnancy zone protein (PZP) is a major pregnancy-associated plasma protein strongly related to alpha2-macroglobulin (alpha2-M). Interactions of tissue plasminogen activator (t-PA) with PZP and alpha2-M were both investigated in vitro and the complexes were analyzed by polyacrylamide gel electrophoresis (PAGE). The results demonstrated that PZP-t-PA complex formation was evident within 1 h of incubation, whereas alpha2-M-t-PA complexes were formed after 18 h. Conclusions were supported by the following e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
11
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 25 publications
1
11
0
Order By: Relevance
“…We and others have previously reported that PZP and human α 2 M show different abilities to interact with proteinases (Arbelaez et al, 1997; Sánchez et al, 1998; Saidi et al, 1999; Ramos et al, 2002). In the present study, we show that both human αMs have similar or complementary functions on NGF‐promoted neurite outgrowth in PC12 cells, but, in rats, activated α 1 M exhibits a neurostimulatory effect (Lee and Koo, 2000), which is clearly different from the neuroinhibitory activity of activated α 2 M (Lee and Koo, 1999).…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…We and others have previously reported that PZP and human α 2 M show different abilities to interact with proteinases (Arbelaez et al, 1997; Sánchez et al, 1998; Saidi et al, 1999; Ramos et al, 2002). In the present study, we show that both human αMs have similar or complementary functions on NGF‐promoted neurite outgrowth in PC12 cells, but, in rats, activated α 1 M exhibits a neurostimulatory effect (Lee and Koo, 2000), which is clearly different from the neuroinhibitory activity of activated α 2 M (Lee and Koo, 1999).…”
Section: Discussionmentioning
confidence: 78%
“…The bait region sequence is markedly different in PZP compared with human α 2 M as well as α 1 M and rat α 2 M, and it is, in fact, the region with the lowest similarity, suggesting different or complementary functions for the proteinase inhibition exerted by these αMs (Garton et al, 1991). In this sense, recently we demonstrated that PZP interacts more quickly than human α 2 M with tissue‐type plasminogen activator (t‐PA), promoting its clearance via the main αM receptor known as low‐density lipoprotein (LDL) receptor‐related protein (LRP) (Sánchez et al, 1998; 2001) and suggesting that PZP, and not α 2 M, may contribute to the control of the activity of proteinases derived from the fibrinolytic system during pregnancy.…”
mentioning
confidence: 99%
“…S100A9 is a cytosolic PMN protein that can be secreted and exhibits potent actions on inflammatory cell recruitment (35). In addition, ␣ 1 - macroglobulin, similar to ␣ 2 -macroglobulin, binds several proteinases including tissue-plasminogen activator and promotes their clearance (36). Thus, it is possible that ␣ 1 -macroglobulin, like ␣ 2 -macroglobulin, also plays a role in the removal of proinflammatory cytokines in the exudate and/or lowering these effective local concentrations before the onset of resolution (37).…”
Section: Discussionmentioning
confidence: 99%
“…However, a 2 M Ã only recognizes LRP1 and not any other LDL receptor members [Hussain et al, 1999]. In addition, a 2 M Ã is internalized by LRP1, implying that both molecules are involved in the modulation of the extracellular activity of several proteases [Sanchez et al, 1998;Herz and Strickland, 2001;Ramos et al, 2002]. LRP1 is a cell surface glycoprotein synthesized as a 600-kDa proreceptor and post-translationally processed into 515-kDa a-subunit and 85-kDa b-subunit that remain associated through non-covalent interactions [Herz and Strickland, 2001].…”
mentioning
confidence: 99%